The determinants of foreign direct investment in African countries - Kariuki, Caroline Wanjiru (Curtin University, 2014)
This research examines the significance of economic risk, financial risk, political risk, commodity price index performance, world stock market index performance, gross fixed capital formation, openness to trade, and the availability of a stock market in a host country in influencing FDI flows into African countries. Thirty five countries are included in this research, which uses panel data analysis. Annual data are used with a time period of 27 years.